2019
DOI: 10.3390/biom9040135
|View full text |Cite
|
Sign up to set email alerts
|

LcNAC13 Physically Interacts with LcR1MYB1 to Coregulate Anthocyanin Biosynthesis-Related Genes during Litchi Fruit Ripening

Abstract: Anthocyanin accumulation is crucial for the development of quality for most fruit. The mechanism underlying the regulation of anthocyanin biosynthesis by transcription factors in litchi fruit remains largely unknown. In this study, we isolated one NAC (NAM, ATAF1/2 and CUC2) TF gene, LcNAC13. Expression of LcNAC13 was upregulated as ripening proceeded, followed by the accumulation of anthocyanins. Electrophoretic mobility shift assay (EMSA) and transient expression assay showed that LcNAC13 could negatively re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…Anthocyanins are synthesized in cytosol, and stored in the vacuole. Studies on several plant species, including Arabidopsis ( Baudry et al, 2006 ; Gonzalez et al, 2008 ; Qi et al, 2011 ; Xie et al, 2016 ), agricultural crops ( Yang et al, 2019 ; Dong et al, 2020 ), fruits ( Rahim et al, 2014 ; Zhou et al, 2015 ; Jiang et al, 2019 ; Li C. et al, 2020 ), vegetable and ornamental plants ( Suzuki et al, 2016 ; Xu et al, 2017 ; Jin et al, 2018 , 2019 ; Zhu et al, 2019 ) have revealed that biosynthesis of anthocyanins are controlled by structural and regulatory genes that take part in formation as well as regulation of specific enzymes. The key enzymes including phenylalanine ammonia lyase (PAL), cinnamic acid 4-hydroxylase (C4H), 4-coumarate-CoA ligase (4CL), chalcone synthase (CHS), chalcone isomerase (CHI), flavonone 3-hydroxylase (F3H), dihydroflavonol 4-reductase (DFR), flavonoid 3′-monooxygenase (F3′H), anthocyanin synthase (ANS), as well as UDP-glucose-flavonoid 3- O -glucosyltrasnferase (UFGT) are important in anthocyanin biosynthesis ( Koes et al, 2005 ; Li et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthocyanins are synthesized in cytosol, and stored in the vacuole. Studies on several plant species, including Arabidopsis ( Baudry et al, 2006 ; Gonzalez et al, 2008 ; Qi et al, 2011 ; Xie et al, 2016 ), agricultural crops ( Yang et al, 2019 ; Dong et al, 2020 ), fruits ( Rahim et al, 2014 ; Zhou et al, 2015 ; Jiang et al, 2019 ; Li C. et al, 2020 ), vegetable and ornamental plants ( Suzuki et al, 2016 ; Xu et al, 2017 ; Jin et al, 2018 , 2019 ; Zhu et al, 2019 ) have revealed that biosynthesis of anthocyanins are controlled by structural and regulatory genes that take part in formation as well as regulation of specific enzymes. The key enzymes including phenylalanine ammonia lyase (PAL), cinnamic acid 4-hydroxylase (C4H), 4-coumarate-CoA ligase (4CL), chalcone synthase (CHS), chalcone isomerase (CHI), flavonone 3-hydroxylase (F3H), dihydroflavonol 4-reductase (DFR), flavonoid 3′-monooxygenase (F3′H), anthocyanin synthase (ANS), as well as UDP-glucose-flavonoid 3- O -glucosyltrasnferase (UFGT) are important in anthocyanin biosynthesis ( Koes et al, 2005 ; Li et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some other TFs such as the MYB-bHLH-WD (MBW) complex, B-box, bZIP, MYC, NAC, WRKY, bHLH, MADS-box, and WD could also coordinate anthocyanin biosynthesis initiation by binding to the promoter regions of structural genes ( Xu et al, 2015 ; Zhou et al, 2015 ; An et al, 2017 ; Lloyd et al, 2017 ; Lu et al, 2018 ; Fang et al, 2019 ; Jiang et al, 2019 ). For example, Arabidopsis bHLH TFs (GL3, TT8, and EGL3) and WD40 repeat protein TTG1 regulate anthocyanin biosynthetic gene expressions ( Gonzalez et al, 2008 ; Gerats and Strommer, 2009 ; Saito et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…MYB10, which belongs to Sg6, performs a key regulating function in anthocyanin biosynthesis through binding to the promoter of anthocyanin biosynthetic structural genes in Malus domestica, Pyrus spp., and Amygdalus persica (Espley et al, 2007;Feng et al, 2010;Zhou et al, 2019). Moreover, researchers have reported that other TFs, such as WRKY, ethylene response factors (ERF), NAC, zinc finger, and MADS-box proteins, are involved in the anthocyanin biosynthetic pathway in Pyrus spp., Litchi chinensis, Arabidopsis, and Brassica napus (Duan et al, 2018;Ni et al, 2018;Jiang et al, 2019). However, there has been little research addressing how genetic information and transcription contribute to the regulation of flower color in Malus spp.…”
Section: Introductionmentioning
confidence: 99%
“…LcR1MYB1 was also highly expressed during fruit ripening, moreover it can interact with LcNAC13 and weaken or even reverse the transcriptional inhibition of LcNAC13 on its target genes. This suggests that LcNAC13 and LcR1MYB1 may antagonistically regulate anthocyanin accumulation during litchi fruit ripening [126].…”
Section: Nac Tfs and Fruit Color Transformationmentioning
confidence: 93%